Systematic review: bile acids and intestinal inflammation‐luminal aggressors or regulators of mucosal defence?. Issue 7 (29th July 2015) - Pavlidis, P.; Powell, N.; Vincent, R. P.; Ehrlich, D.; Bjarnason, I.; Hayee, B.
Summary Background Inflammatory bowel diseases (IBD), comprising Crohn's disease and ulcerative colitis (UC), are chronic conditions attributed to an aberrant immune response to luminal triggers. Recently, published work suggests a pathogenic role for bile acids in this context. Aim To perform a systematic review of studies investigating the role of bile acids in intestinal inflammation and present potentially relevant clinical implications. Methods Pubmed search for English language articles published up to May 2015. Terms used were: 'bile', 'bile acid', 'barrier', 'small bowel injury', 'Crohn's' and 'colitis'. Results Experimental studies support a variable role for bile acids in intestinal barrier homoeostasis. This may be attributed to different physicochemical properties, variable effects on epithelia and immune cells via bile acids‐specific receptors, or through a cross‐talk with the gut microbiome. A reduction in the bile acids pool, with lower concentrations of secondary forms, has been recognised for some time in Crohn's disease and associated to ileal dysfunction and bile acids malabsorption. Recent work suggests that these changes, including an increase in sulphated forms, are related to inflammatory activity in both Crohn's disease and UC. The detrimental effects of 'western diet' elements such as emulsifiers and fat, which have been implicated in the development of the current IBD and obesity epidemics, may also be bile acid‐mediated. Conclusions Although there are only a few observational clinical studies to support an interaction, in vivo human and animal studies support an association between bile acids metabolism, the gut microbiome and intestinal inflammation. This may well prove to have significant diagnostic and therapeutic implications.